'Winter is coming': a COVID‐19 wake‐up call. Issue 5 (23rd September 2020) - Kirby, Roger
Abstract : In this editorial, Roger Kirby, Editor‐in‐Chief for Trends in Urology and Men's Health, discusses why the association between obesity and higher‐risk COVID‐19 infection needs to be taken seriously as we get increasingly close to winter, the prime flu season.